Toy story - Lasseter, John.; Docter, Pete.; Whedon, Joss.; Stanton, Andrew; Ranft, John.; Cohen, Joel.; Sokolow, Alec.; Guggenheim, Ralph; Arnold, Bonnie; Hanks, Tom.; Allen, Tim, 1953-; Rickles, Don.; et al. ([United States] : Disney/Pixar ; Burbank, CA : Distributed by Buena Vista Home Entertainment, Inc., 2005)
Woody the cowboy and Buzz Lightyear, two talking toys, have a fantastic adventure when they go out into the world. This new version contains improved video and audio along with several new bonus features, including all-new games and music videos, new deleted scenes, documentary featurettes, and more.
DVD, region 1, widescreen (1.77:1) presentation; 5.1 DTS surround sound.
English dialogue, French or Spanish subtitles; closed-captioned.
Voices of: Tom Hanks, Tim Allen, Don Rickles, Jim Varney, Wallace Shawn, John Ratzenberger, Annie Potts, John Morris, Erik Von Detter, Laurie Metcalf, R. Lee Ermey, Sarah Freeman.
Music, Randy Newman.
Originally released as a motion picture in 1995.
MPAA rating: G.
Keywords: Toys -- Juvenile drama; Lightyear, Buzz (Fictitious character) -- Juvenile drama; Video recordings for the hearing impaired; Toys -- Drama; Lightyear, Buzz (Fictitious character) -- Drama; Toys -- Juvenile drama; Animated films; Children's films